Optogenetics Neuromodulation of the Nose - Feng Xiang; Shipeng Zhang; Mi Tang; Peijia Li; Hui Zhang; Jiahui Xiong; Qinxiu Zhang; Xinrong Li (Behavioural Neurology)
Recently developed optogenetic technology, which allows high-fidelity control of neuronal activity, has been applied to investigate the neural circuits underlying sensory processing and behavior. The nasal cavity is innervated by the olfactory nerve and trigeminal nerve, which are closely related to common symptoms of rhinitis, such as impairment of smell, itching, and sneezing. The olfactory system has an amazing ability to distinguish thousands of odorant molecules at trace levels. However, there are many issues in olfactory sensing mechanisms that need to be addressed. Optogenetics offers a novel technical approach to solve this dilemma. Therefore, we review the recent advances in olfactory optogenetics to clarify the mechanisms of chemical sensing, which may help identify the mechanism of dysfunction and suggest possible treatments for impaired smell. Additionally, in rhinitis patients, alterations in the other nerve (trigeminal nerve) that innervates the nasal cavity can lead to hyperresponsiveness to various nociceptive stimuli and central sensitization, causing frequent and persistent itching and sneezing. In the last several years, the application of optogenetics in regulating nociceptive receptors, which are distributed in sensory nerve endings, and amino acid receptors, which are distributed in vital brain regions, to alleviate overreaction to nociceptive stimuli, has gained significant attention. Therefore, we focus on the progress in optogenetics and its application in neuromodulation of nociceptive stimuli and discuss the potential clinical translation for treating rhinitis in the future.